PRONOMINA PERSONA DALAM TEKS PERAYAAN EKARISTI DALAM BAHASA JAWA - Zoraida Uma Setiawan; Widhyasmaramurti (PT. Intelek Cendikiawan Nusantara, 2024)
Personal pronouns in Javanese mentioned by Wedhawati (2001), Rahyono (2011), and Suharti et al. (2017) are pronouns used to refer to people. In general, the personal pronouns used depend on the background of the conversation and the social level of the speaker, so understanding the context of reference of the use of personal pronouns is necessary. However, in the text of the Eucharistic celebration, there is a reference to personal pronoun that differs from the established standard, namely in the use of the personal pronoun “kawula” and “dalem”. The purpose of this study is to look at the context behind the reference of personal pronoun in Eucharist text. The method in this research is analysis based on pragmatic theory by Morris (in Yanti, 2019) with data in the form of sentences containing personal pronouns. The data source of this research is obtained from video documentation of the Easter Eucharist of Gereja Paroki St. Theresia Lisieux Boro, Gereja Paroki Hati Kudus Tuhan Yesus Ganjuran, and Gereja Paroki Katedral Purwokerto which was heard and transcribed into written text. The results show that the personal pronouns used have different contexts which include 1) reflecting various levels of familiarity, 2) respect, and 3) formality. Keywords: Eucharist, Javanese, Personal Pronouns, Pragmatic Analysis